Deubiquitylation Regulates Activation and Proteolytic Cleavage of ENaC - Ruffieux-Daidié, Dorothée (American Society of Nephrology, 2008)
The epithelial sodium channel (ENaC) is critical for sodium and BP homeostasis. ENaC is regulated by Nedd4-2–mediated ubiquitylation, which leads to its internalization; this process can be reversed by deubiquitylation, which is regulated by the aldosterone-induced enzyme Usp2-45. In a second regulatory pathway, ENaC can be activated by luminal serine protease–mediated cleavage of its extracellular loops. Whether these two regulatory processes interact, however, is unknown. Here, in HEK293 cells stably transfected with ENaC, Usp2-45 interacted with ENaC, leading to deubiquitylation of the channel and stimulation of ENaC activity >20-fold. This was accompanied by a modest increase in cell surface expression of ENaC and by proteolytic cleavage of αENaC and γENaC at their extracellular loops. When endocytosis was inhibited with dominant negative dynamin (DynK44R), channel density and γENaC cleavage were increased, but αENaC cleavage and ENaC activity were not augmented. When Usp2-45 was coexpressed with DynK44R, both αENaC cleavage and activity were recovered. In summary, these data suggest that Usp2-45 deubiquitylation of ENaC enhances the proteolytic activation of both αENaC and γENaC, possibly by inducing a conformational change and by interfering with endocytosis, respectively.